Symptomatic Adverse Events and Quality of Life Related to Incretin-Based Medicines for Obesity: A Systematic Review Involving >400,000 Subjects - Robert F. Kushner; Odd Erik Johansen; Krysmaru Araujo Torres; Trà-Mi Phan; Agnieszka Marczewska (Obesities, 2025)
Background/Objectives: Obesity is a chronic, progressive, recurrent disease associated with impaired health, affecting an increasing proportion of the population worldwide. Newer-generation incretin-based therapies (IBTs) (liraglutide, semaglutide, and tirzepatide) have shown greater efficacy than older anti-obesity medications. This systematic literature review provides an overview of the evidence on the symptomatic adverse events (AEs) and patient-reported outcomes of IBTs to facilitate clinical decision-making. Methods: A systematic search was conducted using a predefined search strategy to identify controlled trials and real-world evidence (RWE) studies assessing IBTs. Results: Among 4414 publications identified, 81 (>400,000 participants) were included. Liraglutide (n = 49), semaglutide (n = 34), and tirzepatide (n = 7) were used in 48 clinical and 33 RWE studies. Gastrointestinal (GI) AEs were most common: placebo-subtracted incidences were 5–39% for nausea, −7–39% for diarrhea, 2–31% for constipation, 0–26% for vomiting, and 2–20% for abdominal pain, with no clear difference across IBTs. Most AEs were mild or moderate and mainly occurred during dose escalation. Quality of life outcomes were reported in 27 publications and generally showed improvements with IBTs. Conclusions: This study confirms that GI AEs are common with IBTs. Clinicians should keep the AE profile of IBTs in mind and consider where additional preventative measures may be required.